2016
DOI: 10.1039/c6cp05253c
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of ice nucleation events on individual atmospheric particles

Abstract: The work presents microscopic observations of heterogeneous ice nucleation from experiments conducted inside an environmental scanning electron microscope. Observations of ice formation on kaolinite particles demonstrate that ice preferentially nucleates at the edges of the stacked platelets, rather than on the basal planes. This platform is applied for directly detecting and tracking ice nucleating particles in ambient aerosol samples and is complemented by micro-spectroscopic chemical imaging. This technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 84 publications
6
86
0
Order By: Relevance
“…However, the correlation between lattice match and nucleation is in general not strong (29), and there is a wide scatter in the reported nucleating abilities of atmospheric aerosols (30). The mechanism of ice nucleation in capillary-condensed water that was proposed 50 y ago by Fukuta has only recently been revisited (31,32), but it has already been suggested that it contributes to the ice nucleation capacity of kaolinite (33,34) and leads to enhanced ice nucleation by porous aerosol particles (35,36). It is also noteworthy that alkali feldspars, which have been shown to be particularly efficient ice h is the predicted size of a liquid condensate at saturation with respect to a solid.…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between lattice match and nucleation is in general not strong (29), and there is a wide scatter in the reported nucleating abilities of atmospheric aerosols (30). The mechanism of ice nucleation in capillary-condensed water that was proposed 50 y ago by Fukuta has only recently been revisited (31,32), but it has already been suggested that it contributes to the ice nucleation capacity of kaolinite (33,34) and leads to enhanced ice nucleation by porous aerosol particles (35,36). It is also noteworthy that alkali feldspars, which have been shown to be particularly efficient ice h is the predicted size of a liquid condensate at saturation with respect to a solid.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ice nucleation ability of an ice-nucleating particle may be influenced by the change in surface properties due to aging (Coluzza et al, 2017) or other secondary ice processes (Zipori et al, 2018). Solutes are able to affect freezing (Zobrist et al, 2008), even at low concentrations (Whale et al, 2018). Depending on the atmospheric conditions, water molecules may heterogeneously crystallize next to an icenucleating particle surface, forming various ice polymorphs with different physical and/or surface properties (Parambil et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the configuration of ESEM makes it feasible to design in situ experiments of phase transitions of water, in case of the rational controlling over the chamber temperature and pressure. For example, the icing process of water and the melting process of ice, which can provide the fundamentals for phase transitions of water, are frequently observed and examined by in situ ESEM experiments in terms of structural and morphological changes . Kiselev et al investigated the nucleation and growth of aligned ice crystals from water vapor on feldspar (an atmospherically important component of mineral dust) under ESEM to clarify the dominate reason in regulating the ice‐nucleation properties on specific substrates.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…For example, the icing process of water and the melting process of ice, which can provide the fundamentals for phase transitions of water, are frequently observed and examined by in situ ESEM experiments in terms of structural and morphological changes. [9,[104][105][106] Kiselev et al investigated the nucleation and growth of aligned ice crystals from water vapor on feldspar (an atmospherically important component of mineral dust) under ESEM to clarify the dominate reason in regulating the ice-nucleation properties on specific substrates. The observation was conducted in an ESEM with a double-stage Peltier element, with its low temperature limit down to 213 K. The results gave a direct experimental evidence to indicate that the active sites for ice-nucleation on the surface of feldspar are the surface patches with (100) crystallographic orientation.…”
Section: Phase Transitions Of Watermentioning
confidence: 99%